Glucocerebroside-Containing Milk Concentrated Powder Suppresses Oxidative Stress and Photoaging in the Skin of Hairless Mice - Dakyung Kim; Eun-hye Choi; Ju Young Lee; Hye-Jeong See; Hye-Jin Kim; Yunhi Cho; Ok-Kyung Kim; Jeongmin Lee (MDPI AG, 2022)
This study investigated the protective effects of glucocerebroside-containing buttermilk concentrated powder (GCBM) on oxidative stress and photoaging in ultraviolet B (UVB)-irradiated hairless mice. We measured antioxidant enzyme activities, collagen synthesis-related pathways, and moisturizing-related factors in the dorsal skin of mice. We observed that dietary supplementation with GCBM increased antioxidant enzyme activity and decreased pro-inflammatory cytokine expression in the UVB-irradiated dorsal skin. Furthermore, dietary supplementation with GCBM inhibited wrinkle formation by suppressing the JNK/c-FOS/c-Jun/MMP pathway and stimulating the TGF-βRI/Smad3/procollagen type I pathway. Dietary supplementation with GCBM also increased skin moisturization by stimulating hyaluronic acid and ceramide synthesis in the dorsal skin. Therefore, buttermilk powder supplementation helps prevent photoaging and can be used as an effective component in developing anti-photoaging products.